Intra-sinus complex odontoma management simultaneously to oroantral communication closure: Why remove it? (Research, Society and Development, 2021)
The oroantral communication is considered one of the most frequent complications in oral surgery, especially in extractions of posterior teeth in the maxilla, treatment of cystic lesions, neoplasms, osteomyelitis and trauma in the region of the maxillary sinus, forming fistulas. However, ectopic third molar and lesions such as odontomas are rarely found simultaneously in the maxillary sinus. This report shows a successful treatment performed in a specific case of oroantral communication, associated to an underdiagnosed complex odontoma and an impacted ectopic third molar into the maxillary sinus and discuss the requirement of intervention. The treatment strategy involved clinical and surgical management through the oroantral communication, avoiding additional bone access to the maxillary sinus. This proposal presented a satisfactory result, and at six months after surgery, the patient has an excellent evolution, proving to be a successful strategy.